FENOMENA DISPARITAS PENGELOLAAN KELAS ANTARA SD NEGERI DAN SWASTA UNGGULAN DI TEGAL - Yawart, Ulfa Khasanah; Bakti, Ageng; Sari, Resta Rahma (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2019)
Abstract:. Class management or class management is a conscious effort of a teacher to organize learning activities systematically. Class management is a factor that has the first position as a determinant of student learning outcomes. This study aims to determine the effect of class management between Primary and Private Primary Schools in Tegal. The method used in this study is to use qualitative-quantitative methods. . The object of this study was grade 2 students at the Mendangusuman Public Elementary School (SDK 1) and class 1 SD Pelita Harapan Bangsa (PHB). Data collection techniques in this study used observation, interviews, questionnaires, and documentation techniques. Whereas to analyze the data obtained, researchers used the SPSS version 23.0 statistical program with the results of data analysis stating that the average teacher's ability in classroom management in MKK 1 SDN was 68.52 and in PHB SD was 88.77. While the student learning outcomes in MKK 1 SDN amounted to 94.32 with the lowest score of 86 and the highest score of 100. And for the learning outcomes in elementary school PHB amounted to 98.15 with the lowest score 89 and the highest score of 100.Keyword: Class management, elementary schoolÂ Abstrak: Pengelolaan kelas atau manajemen kelas merupakan usaha sadar seorang guru untuk mengatur kegiatan pembelajaran secara sistematis. Pengelolaan kelas merupakan faktor yang mempunyai kedudukan pertama sebagai penentu hasil belajar siswa. penelitian ini bertujuan untuk mengetahui pengaruh pengelolaan kelas antara SD Negeri dan SD Swasta Unggulan di Tegal. Metode yang digunakan dalam penelitian ini adalah dengan menggunakan metode kualitatif-kuantitatif. . Objek penelitian ini adalah siswa kelas 2 SD Negeri Mangkukusuman (MKK) 1 dan kelas 1 SD Pelita Harapan Bangsa (PHB). Teknik pengumpulan data dalam penelitian ini menggunakan teknik observasi, wawancara, angket, dan dokumentasi. Sedangkan untuk menganalisis data yang didapat, peneliti menggunakan program statistik SPSS versi 23.0 dengan hasil analisis data menyatakan rata-rata kemampuan guru dalam pengelolaan kelas di SDN MKK 1 adalah 68,52 dan di SD PHB sebesar 88,77. Sedangkan hasil belajar siswa pada SDN MKK 1 sebesar 94,32 dengan nilai terendah 86 dan nilai tertinggi 100. Dan untuk hasil belajar pada SD PHB sebesar 98,15 dengan nilai terendah 89 dan nilai tertinggi 100.Kata Kunci: Pengelolaan kelas, Sekolah dasar